Promoting livelihood and economic growth through agroforestry: ICFRE endeavours - Gera, Neelu; Bhojvaid, P.P. (Indian Journal of Agroforestry, 2020)
Proper management of inputs and interventions can increase productivity many folds.Adopting appropriate production technology in terms of tillage operations, fertilizer application, appropriate designs, diversification, biotechnology, genetic improvement and selection of the most economically and ecologically suitable species are of paramount importance.The agroforestry should be looked upon as a means for improving socio-economic conditions of the rural poor and should be the main components of an integrated rural development programme. In order to increase fuel, timber and forage production, agroforestry programmes should be adopted on a large scale.